Modelling the agronomic and environmental impacts of irrigation management on turfgrass for golf greens in northern europe. - Gomez-Armayones, Carlos (Cranfield University, 2018)
Irrigation is an essential component of turfgrass management for golf. During dry periods, it helps maintain turf health, stimulates nitrogen uptake, promotes germination, reduces canopy temperature, as well as assures high standards of quality for playability. In recent years, rising competition for water coupled with new environmental regulations has exerted pressure on water allocations for golf. Improving water efficiency and water management in golf have become major industry priorities. The aim of this thesis was to understand and asses the relationships between irrigation management and turfgrass water use, soil water availability, dry matter production, drainage and nitrate leaching in golf greens under Northern European climate conditions. The research combined published science and industry evidence with field and experimental data, in order to calibrate and validate an irrigation ballistics-based model and a biophysical crop model (STICS). From this, an integrated model (BalliSTICS) was developed and used to simulate the impacts of irrigation uniformity on turfgrass growth and development and leaching risks, under contrasting management and climate scenario. The modelling showed that system design plays a crucial role in achieving high irrigation uniformity, particularly sprinkler position and spacing. A larger spacing between sprinklers resulted in a decrease in irrigation rates and a significant decrease in uniformity, particularly when wind speeds exceeded 2 m s-1. Surprisingly, the range of pressure and nozzle sizes investigated did not significantly impact on irrigation uniformity. Non-uniform irrigation was found to have a considerable impact on the spatial variability in turf growth, soil moisture content, drainage and leaching. Under northern European climate conditions, irrigation strategy had a more significant impact on turfgrass response than irrigation uniformity. A moderate deficit strategy (replacement of 60% potential evapotranspiration) was sufficient to achieve the highest growth values (233 ± 10.6 g m-² season¯¹). This strategy resulted in not only a reduction of irrigation water use but also minimised the amount of nitrate leached in drainage. However, an inadequate irrigation schedule combined with poor irrigation uniformity (CU < 60%) led to a threefold increase in water use, and an average 114% and 50% increase in drainage and nitrate leaching, respectively. Inadequate irrigation practices had little impact on turfgrass growth, which could be misleading as excessive irrigation might not affect plant growth and visual quality but would mask poor irrigation uniformities, lead to excessive water use and an increase in risks of groundwater contamination from leaching. The research provides valuable and novel insights into better understanding the combined impacts of irrigation performance and management on turfgrass. The findings will support greenkeepers and the turfgrass industry and increase awareness of the importance of irrigation.
Keywords: Irrigation scheduling; irrigation uniformity; leaching; modelling; turfgrass